Satellite television use among Zimbabwean professionals : an investigation into audience consumption of SABC Africa's '60 Minutes live in Africa' - Mugoni, Petronella Chipo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
Within the context of debates surrounding the consumption of global media by local audiences in Third World countries, this study explores the reasons behind satellite television subscription, and consumption of international news among a sample of young professional men and women in contemporary Zimbabwe. The study seeks to uncover how the research participants respond to news broadcast on SABC Africa's '60 minutes live in Africa', a programme which they can only access via satellite television in their country. Working within the frame of audience studies which insists on understanding media consumption and reception in context, this study examines how the respondents, situated within the specific Zimbabwe context, characterised as it is by serious social, economic and political challenges, respond to both regional news and news about their country on '60 minutes live in Africa'. Within the frame of qualitative research the study employs a two-stage sampling procedure and data collection strategy to uncover the factors that underpin international media consumption and reception by professional men and women situated in a country undergoing rapid change. The findings of the study point to the various social and individual factors that underlie media consumption choices as well as to the different socially patterned reasons why local audiences are either attracted to, or reject global media. The study found that SABC Africa's '60 minutes live in Africa' is more popular and better received than Western-broadcast programmes on channels such as BBC, CNN, and Sky News among Zimbabwean professionals. I also uncovered some evidence that cultural proximity and relevance are of supreme importance in determining which media audiences chose to consume and what level of engagement they bring to their reception of global media. These and other findings directly confront media models that privilege beliefs in cultural imperialism and the dominance of Western media and their effects on Third World audiences.
Keywords: Direct broadcast satellite television -- Zimbabwe; Television viewers -- Zimbabwe; Television viewers -- Zimbabwe -- Case studies; Television broadcasting of news -- Zimbabwe